Constructed wetlands treating stormwater from separate sewer networks in a residential Strasbourg urban catchment area: Micropollutant removal and fate. Issue 4 (December 2015) - Schmitt, Noëlle; Wanko, Adrien; Laurent, Julien; Bois, Paul; Molle, Pascal; Mosé, Robert
Abstract: A full-scale treatment system made of a sedimentation pond followed by a subsurface flow constructed wetland has been set up to collect stormwater from an urban residential watershed. Despite the high variability of hydraulic and pollutants loads, high removal efficiencies for TSS (>90%), COD (70–98%) and nutrients (TN > 79%; TP > 77%) have been observed. The pond contributes to particulate pollution mitigation in large quantities (55–92% of TSS): particle-bound micro-pollutants (metals, PAHs) are then mainly removed there; the vertical subsurface flow constructed wetland allows removal of the remaining particulate fraction through filtration. Experimental data show that metals are retained in the pond and the filter whereas PAHs are retained in the pond only. Biochemical transformations seem to occur, decreasing soluble COD and nutrient concentrations. Finally, micropollutants concentrations in sediments, sand and plants allow estimating storage in constructed wetland compartments.